106k views
4 votes
If m^2-5/2m=-11/2,m=

Plz answer fast!!!

If m^2-5/2m=-11/2,m= Plz answer fast!!!-example-1
User Pxlshpr
by
5.3k points

2 Answers

2 votes

Answer:


m = \frac { 5 } { 4 } \pm\frac { 3 } { 4 } i \sqrt { 7 }

Explanation:

We are given the following equation and we are to solve it for m:


m ^ 2 - \frac { 5 } { 2 } m = - \frac { 1 1 } { 2 }

We will solve this using the quadratic formula
(-b\±√(b^2-4ac))/(2a).

Rearranging the equation to get:


m^2-(5)/(2)m+(11)/(2)=0

Substituting the given values in the above formula to get:


m=\frac{-(-(5)/(2))\±\sqrt{(-(5)/(2))^2-4(1)((11)/(2))}}{2*1}\\\\m=\frac{(5)/(2)\±\sqrt{-(63)/(4)}}{2}

We know that
√(-1)=i.


m=((5)/(2)\±(3)/(2)i√(7))/(2)\\\\m=(5)/(4)\±(3)/(4)i√(7)

User Rabin Poudyal
by
5.7k points
2 votes

Answer:
m=(5)/(4)\±(3)/(4)i√(7)

Explanation:

Use the Quadratic formula:


m=(-b\±√(b^2)-4ac)/(2a)

Given the quadratic equation
m^2-(5)/(2)m=-(11)/(2)

Make it equal to zero:


m^2-(5)/(2)m+(11)/(2)=0

You can see that :


a=1\\b=-(5)/(2)\\\\c=(11)/(2)

Substitute values:


m=\frac{-(-(5)/(2))\±\sqrt{(-(5)/(2))^2-4(1)((11)/(2))}}{2*1}\\\\m=\frac{(5)/(2)\±\sqrt{-(63)/(4)}}{2}\\\\m=((5)/(2)\±(3)/(2)i√(7))/(2)\\\\m=(5)/(4)\±(3)/(4)i√(7)

(Remember that
√(-1)=i)

User HenryZhang
by
4.6k points